Fetomaternal outcome in pregnancy with oligohydroamnios - Shihora, Kartavyakumar Y.; Vaghasiya, Meera B.; Ahya, Manali P.; Panchal, Vaishali P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Oligohydramnios is one of the major causes of perinatal morbidity and mortality. The sonographic diagnosis of oligohydramnios is usually based on an AFI≤5 cm or on a single deepest pocket of amniotic fluid≤2 cm. Our study was aimed to study the perinatal outcome in oligohydramnios. Aim and objective were to study obstetric risk factors associated with oligohydramnios and maternal outcome in the form of mode of delivery, and to assess neonatal complications in terms of APGAR score at birth, NICU admission rates, meconium stained liquor and still birth rates. Methods: Present study is a prospective study on outcome of pregnancy in oligohydroamnios. Study was conducted at department of obstetrics and gynaecology at SMT SCL general hospital, Ahmedabad from January 2024 to July 2024. A total of 60 women singleton pregnancy with oligohydroamnios (AFI <5) in third trimester admitted as either booked or referral cases, were included in the study. Results: The present study is of 60 cases of oligohydramnios in this study caesarean section rate was higher in 20-25 years age group and operative morbidity is more common in primipara group. Most common cause of oligohydramnios is idiopathic followed by post-date. LSCS rate is significantly higher in non-reactive NST group. Most common indication to perform caesarean section was fetal distress. Conclusions: AFI is an important and convenient screening test for prediction of perinatal outcome. In presence of oligohydramnios, the risk of fetal distress, operative delivery, low Apgar score, low birth weight, perinatal morbidity and mortality are more. Hence early detection of oligohydramnios, associated antenatal risk factors and timely management can improve the maternal and fetal outcome.